Impact of body‐surface area on patients' outcome in younger adults with acute myeloid leukemia. (1st March 2017) - Cahu, Xavier; Carré, Martin; Recher, Christian; Pigneux, Arnaud; Hunault‐Berger, Mathilde; Vey, Norbert; Chevallier, Patrice; Delaunay, Jacques; Gyan, Emmanuel; Lioure, Bruno; Bonmati, Caroline; Himberlin, Chantal; et al.
Abstract: Objectives: Anthracyclines and cytarabine are cornerstones for intensive chemotherapy in acute myeloid leukemia (AML). The goals of this study were to comprehensively assess deviations from theoretical doses and the impact of body‐surface area (BSA) on patients' characteristics, physicians' strategy, dose adjustment, and clinical outcome. Methods: The GOELAMS 2001 phase III trial included 823 AML patients below 60 years of age. In the course of treatment, anthropomorphic parameters and chemotherapy doses were prospectively registered. Results: Very high BSA (≥2.15 m 2 ) was the factor most significantly associated with the physician's decision to reduce chemotherapy doses during induction and postremission therapy. Despite similar AML characteristics and therapeutic strategies, the very high BSA group exhibited a significantly worse survival (5‐years OS of 27%) compared to the low (BSA≤1.5 m 2 ), intermediate (1.5 m 2 <BSA≤2.0 m 2 ), or high (2 m 2 <BSA<2.15 m 2 ) BSA groups (46%, 47%, 56%, respectively) ( P =.009). In the very high BSA group, dose capping was associated with worse overall survival, although not significantly ( P =.09). Conclusion: The presence of a very high BSA is the main reason prompting physicians to reduce chemotherapy doses in adult AML. Furthermore, these patients display a poor outcome and could benefit from full doses calculated on actual BSA.